Concurrent Training for Women in Menopause: Protocol of a Randomized Controlled Clinical Trial - Fausto D.Y.* (2022)
© 2022 Bentham Science Publishers.Objective: To propose a concurrent training protocol and evaluate the effects on depressive symptoms, anxiety, mood, sexual function, body fat, muscular strength, cardiorespiratory capability, and hormonal profile of women in menopause through a randomized controlled trial. Methods: This is a randomized clinical trial of two arms with 6 months of intervention with concurrent training with menopausal women (40 to 59 years old) with positive symptomatology to the Menopause Rating Scale (MRS) questionnaire and blood collection of Follicle Stimulating Hormone (FSH) ≥25 UI/ml, being randomly and distributed in two groups: experimental group (EG) and control group (CG). In the first trimester, there will be 30 minutes of aerobic training and 30 minutes of resistance training; in the second trimester, 40 minutes of aerobic training and 20 minutes of resistance training. The weekly frequency will be 3 times a week, with sessions lasting 60 minutes, going through a period of neuromuscular adaptation. The intensity will be increased each month according to individual needs. The control group will maintain its activities, normally receiving monthly calls to control and monitor its usual daily activities. Main Outcome Measures: Comparative analyzes will be applied between the results of EG and CG after the intervention period, and also pre-and post-intragroup tests within both groups in order to observe possible changes after the intervention. Conclusion: It is believed that this protocol is capable of treating the psychological, physical symptoms, hormonal profile, and sexual function of menopausal women.